Manajemen Sumber Daya manusia Perspektif Pendidikan Islam dalam Membangun Pendidikan - Ibrahim, Ibrahim (Jurnal Sakinah, 2020)
Human resource management is often nonhumanly conceptualized and implemented, it does not arise from a complete human concept with physical, nafsiyah and spiritual dimensions. In the end, whatever the human side is, it is only measured by material value. This paper describes the concepts, functions and responsibilities of human resource management as well as several efforts to improve human resources in the perspective of Islamic education